P110 Feasibility of continuous laryngoscopy during provocation in the assessment of inducible laryngeal obstruction. (15th November 2017) - Selby, J; Cullinan, P; Feary, J; Scadding, G; Fitzgerald, B; Hull, JH
Abstract : Introduction: Inducible laryngeal obstruction (ILO) is typically provoked by a range of stimuli, including perfumes and exercise, and characterised by transient throat tightness, dyspnoea and stridor. Central to the diagnosis of ILO is paradoxical adduction of laryngeal structures on inspiration. Continuous laryngoscopy during exercise (CLE) is now established as the gold-standard diagnostic test for exercise-ILO, but diagnosis of other forms of ILO is currently dependent on non-continuous laryngeal visualisation, where crucial diagnostic behaviour of the larynx may be missed. We report the first application of continuous laryngoscopy during provocation (CLP). Methodology: Fifteen female patients (aged 36–58) suspected of having ILO and referred from the RBH specialist upper airway clinic underwent CLP, using self-selected provocation agents to elicit their typical symptoms. Three patients had a prior confirmed diagnosis of asthma. The flexible nasendoscope (CMOS, Karl Storz) was passed without anaesthetic and secured on specialist headgear (figure 1 ). Patients entered a sealed provocation booth, where they were exposed to the agents they had selected, unable to see the monitor. On elicitation of upper airway symptoms, the specialist SLT initiated laryngeal control strategies with visual biofeedback. The test ended when the patient's typical symptoms had been generated or when exposure exceeded the point of previous symptom provocation. Results: All patients tolerated continuous placement of the scope and confirmed that exposure in the chamber had been sufficiently concentrated to provoke typical symptoms. Only one patient exhibited classical paradoxical glottic movement. Pre-exposure, the vocal cords were closely adducted in three (20%) patients and fully adducted during unintentional breath-holding in three patients (20%). All patients subsequently attended a review with the specialist SLT to consolidate understanding of CLP findings and use of control strategies. Conclusion: CLP is a safe and well-tolerated method for evaluating laryngeal movement during provocation and negates repeated passage of the nasendoscope. Continuous monitoring throughout provocation testing improves diagnostic accuracy by capturing the presence or absence of paradoxical movement and may be linked with software that tracks laryngeal movement digitally. Further work is needed to develop standardised CLP protocols and identify clinical phenotypes of ILO.